2018
DOI: 10.4274/tjod.55491
|View full text |Cite
|
Sign up to set email alerts
|

Are the skin scar characteristics and closure of the parietal peritoneum associated with pelvic adhesions?

Abstract: Objective:To assess whether the abdominal scar characteristics and closure of the peritoneum were associated with pelvic adhesions.Materials and Methods:Patients who had undergone cesarean section between December 2015 and February 2016 were assessed prospectively in terms of age, gravida, body mass index, number of living children, number of cesarean sections, time passed since the last cesarean section, closure status of the peritoneum in the last cesarean section, presence of other diseases, smoking status,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 27 publications
1
10
0
1
Order By: Relevance
“…In a systemic review of 29 trials published by Bamigboye et al [18] limited and inconsistent evidence was found regarding the relationship between adhesion formation and closure versus non-closure, while the non-closure technique was associated with shorter surgical time [18] Neither of the demographic factors in this study was found to be associated with the severity of adhesions. This is similar to the results found by Taylan et al [2] Stocker et al [11] and Çim et al [19]. The current study attempted to apply two skin markers together, each of which had previously been taken by other researchers as separate factors.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In a systemic review of 29 trials published by Bamigboye et al [18] limited and inconsistent evidence was found regarding the relationship between adhesion formation and closure versus non-closure, while the non-closure technique was associated with shorter surgical time [18] Neither of the demographic factors in this study was found to be associated with the severity of adhesions. This is similar to the results found by Taylan et al [2] Stocker et al [11] and Çim et al [19]. The current study attempted to apply two skin markers together, each of which had previously been taken by other researchers as separate factors.…”
Section: Discussionsupporting
confidence: 86%
“…Many of the abdominal scar features were considered to have an association with adhesions by many authors, such as Çim et al, who found that depressed scars with hypopigmentation are associated with adhesions [19]. Pergialiotis et al [20] undertook a meta-analysis of several observational studies and concluded that depressed scars were positively associated with intra-abdominal adhesions, while flat scars were predictive of the absence of adhesions.…”
Section: Discussionmentioning
confidence: 99%
“…Scar width and appearance showed significant association with dense intraperitoneal adhesions ( p -value 0.001, and 0.002 respectively) [ 10 ]. Depressed hypopigmented scars were also associated with adhesions, which were assumed to arise from the inward traction from the adhesion bands [ 19 , 20 ]. Besides, in a meta-analysis of numerous studies, they reported that flat scars were indicative of absent adhesions while depressed ones were associated with adhesions [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Scar width and appearance showed signi cant association with dense intraperitoneal adhesions (p-value 0.001, and 0.002 respectively) (15). Depressed hypopigmented scars were also associated with adhesions, which were assumed to arise from the inward traction from the adhesion bands (17,18). Besides, in a meta-analysis of numerous studies, they reported that at scars were indicative of absent adhesions while depressed ones were associated with adhesions (19).…”
Section: Discussionmentioning
confidence: 97%